Inter- and Intra-individual Variability in Brain Oscillations During Sports Motor Imagery - Wriessnegger, Selina C.; Müller-Putz, Gernot R.; Brunner, Clemens; Sburlea, Andreea I. (Frontiers in Human Neuroscience, 2020)
The aim of this work was to re-evaluate electrophysiological data from a previous study on motor imagery with a special focus on observed inter-individual differences. More concretely, we investigated event-related desynchronization/synchronization (ERD/S) patterns during sports motor imagery (playing tennis) compared to simple motor imagery (squeezing a ball) and discovered high variability across participants. Thirty healthy volunteers were divided in two groups; the experimental group (EG) performed a physical exercise between two imagery sessions, the control group (CG) watched a landscape movie without physical activity.We estimated inter-individual differences by assessing dissimilarities for each group, condition, time period and frequency band. Whereas ERD/S values are consistent throughout different conditions and time points within many participants, results differ widely between individuals. Especially ERD/S values in the alpha frequency band show high variability within and among the subjects for either group compared to the beta frequency band. Furthermore, distance measures between subject-specific ERD/S patterns show that some pairs of participants are more similar, indicated by smaller distances, than others. For both alpha and beta bands, we found that the median distances across groups, conditions and time periods indicate differences between subjects. Moreover, the range of the variability was larger for the alpha band than for the beta band. In other words, when assessing the distance between a pair of subjects in terms of the ERD/S values in the alpha band, we find subjects that show strong (dis)similarities with others, while in the beta band the magnitude of these (dis)similarities is less pronounced. With this study, we would like to draw attention to variability measures instead of primarily focusing on the identification of common patterns across participants, which often do not reflect neurophysiological reality.